Product development in the wood industry with quality function deployment method - Šivic, Matjaž (Les (Ljubljana), 2020)
The future of the Slovenian wood industry lies in flexible production, which is able to quickly develop and produce high-quality and competitive products. We used the quality function deployment method to develop a new product. The research was completed by building a house of quality matrix. This was carried out by determining the technical requirements of the product that optimally fit the target group of costumers, while taking into account the technological capabilities and economic requirements of the company. The survey showed that customers want to be able to make choices, so they can achieve maximum satisfaction in adapting the product to their needs and desires. This is especially important because certain features of the product have a greater impact on their purchase decisions. In the case of dining tables, these are primarily the size, material and surface treatment. The marketing strategy for new product should also work to highlight some strengths of the product which are not noticeable to costumers at first glance.
Keywords: dining table; jedilna miza; lesna industrija; metoda razvoja funkcij kakovosti; product development; quality function deployment method; razvoj izdelka; wood industry